Therapeutic Presence : a Mindful Approach to Effective Therapy - Geller, Shari M. (American Psychological Association, 2012)
"The therapeutic relationship is essential to positive outcomes of psychotherapy. In this book, Shari Geller and Leslie Greenberg argue that therapeutic presence is the fundamental underlying quality of the therapeutic relationship and, hence, effective therapy. Therapeutic presence is the state of having one's whole self in the encounter with a client by being completely in the moment on a multiplicity of levels--physically, emotionally, cognitively, and spiritually. Present therapists become aware of both their own experience and that of their client through bodily sensations and emotions, and this awareness helps them to connect deeply with the client. Therapeutic presence is not a replacement for technique, but rather a foundational therapeutic stance that supports deep listening and understanding of the client in the moment. Geller and Greenberg present their empirically based model of therapeutic presence that integrates three aspects of the concept: how present therapists prepare for presence both pre-session and in general life; what activities therapists engage in when being therapeutically present; and what in-session presence feels like. The authors also provide a therapeutic presence theory of relationship based on research and clinical wisdom. Importantly, because presence is a learnable state that can be cultivated with practice and commitment, the authors infuse the book with practical, experiential exercises for cultivating presence"--Publicity materials. (PsycINFO Database Record (c) 2011 APA, all rights reserved).